2022
DOI: 10.3389/fpsyg.2022.998321
|View full text |Cite
|
Sign up to set email alerts
|

Elements of musical and dance sophistication predict musical groove perception

Abstract: Listening to groovy music is an enjoyable experience and a common human behavior in some cultures. Specifically, many listeners agree that songs they find to be more familiar and pleasurable are more likely to induce the experience of musical groove. While the pleasurable and dance-inducing effects of musical groove are omnipresent, we know less about how subjective feelings toward music, individual musical or dance experiences, or more objective musical perception abilities are correlated with the way we expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…Sensitivity to groove (how well one can distinguish high-groove music from low-groove music) is also reported to be related to musical and dance sophistication, as assessed by the scores of Musical Training and Perceptual Abilities of the Goldsmith Music Sophistication Index and Social Dancing of the Goldsmith Dance Sophistication Index (O'Connell et al, 2022). Another study revealed that while dancers and non-dancers did not significantly differ in their ratings of groove and the optimal level of syncopation for groove, the inverted-U shaped relationship was stronger in dancers (Cameron, et al, 2022a).…”
Section: Musical Trainingmentioning
confidence: 99%
“…Sensitivity to groove (how well one can distinguish high-groove music from low-groove music) is also reported to be related to musical and dance sophistication, as assessed by the scores of Musical Training and Perceptual Abilities of the Goldsmith Music Sophistication Index and Social Dancing of the Goldsmith Dance Sophistication Index (O'Connell et al, 2022). Another study revealed that while dancers and non-dancers did not significantly differ in their ratings of groove and the optimal level of syncopation for groove, the inverted-U shaped relationship was stronger in dancers (Cameron, et al, 2022a).…”
Section: Musical Trainingmentioning
confidence: 99%